1997
DOI: 10.1177/002221949703000304
|View full text |Cite
|
Sign up to set email alerts
|

Gifted Children with Learning Disabilities: A Review of the Issues

Abstract: Many people have difficulty comprehending that a child can be gifted and also have learning disabilities. As a result, children with special needs that result from both their high abilities and their learning problems are rarely identified and are often poorly served. This article explores the current policies and practices with regard to defining, identifying, and educating this population. Recommendations are included that would help ensure that students who are gifted and have learning disabilities receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
249
1
15

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(267 citation statements)
references
References 50 publications
2
249
1
15
Order By: Relevance
“…This situation, which is the main caused of misdiagnoses of the gifted, has been discusses in length (e.g. Brody & Mills, 1997;Ellston, 1993;Fall & Nolan, 1993;Reynoldset al, 1993;Siegel & Metsala, 1992).…”
Section: Faye's Psychological Diagnosis At Agementioning
confidence: 99%
“…This situation, which is the main caused of misdiagnoses of the gifted, has been discusses in length (e.g. Brody & Mills, 1997;Ellston, 1993;Fall & Nolan, 1993;Reynoldset al, 1993;Siegel & Metsala, 1992).…”
Section: Faye's Psychological Diagnosis At Agementioning
confidence: 99%
“…To do all these, teachers must have the opportunities to tap the full potentials of both the diligent and the intelligent children. Failure on their part to tap into their pupils' potentials fully might result to severe and grave consequences (Brody & Mills, 1997).…”
Section: Final Thoughtsmentioning
confidence: 99%
“…In a study by Brody and Mills (1997), it was pointed out that those students with LDs should develop creative thinking to be able to overcome and contend with all the difficulties that they face during attainment of education. Recently, many studies have shown an improvement in the thinking abilities with others variables among students with difficulties (Al Zyoudi, 2009;Alqemish et al, 2007;Kattab & Al Hadid, 2008;Leshowitz et al, 1993;Monahan, 2000).…”
Section: International Journal Of Academic Research In Progressive Edmentioning
confidence: 99%